2019
DOI: 10.1371/journal.pone.0211482
|View full text |Cite
|
Sign up to set email alerts
|

Community health workers trained to conduct verbal autopsies provide better mortality measures than existing surveillance: Results from a cross-sectional study in rural western Uganda

Abstract: Background In much of sub-Saharan Africa, health facilities serve as the primary source of routine vital statistics. These passive surveillance systems, however, are plagued by infrequent and unreliable reporting and do not capture events that occur outside of the formal health sector. Verbal autopsies (VA) have been utilized to estimate the burden and causes of mortality where civil registration and vital statistics systems are weak, but VAs have not been widely employed in national surveillance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 21 publications
0
15
0
Order By: Relevance
“…Although CHWs were trained for the selected zoonoses or participated in the zoonoses campaigning in the local setting, they urged for more intense OH training before being captivated as OHAs. Although the evidence already indicates the involvement of CHWs in pandemic control [ 54 ] and their multidisciplinary roles in infectious disease control [ 55 ] and surveillance [ 56 ], CHWs urged for more OH training on multidisciplinary teamwork. Thus, the OH training should strengthen social and leadership skills, as well as training on coordinating roles in a multidisciplinary team along with the subject knowledge.…”
Section: Discussionmentioning
confidence: 99%
“…Although CHWs were trained for the selected zoonoses or participated in the zoonoses campaigning in the local setting, they urged for more intense OH training before being captivated as OHAs. Although the evidence already indicates the involvement of CHWs in pandemic control [ 54 ] and their multidisciplinary roles in infectious disease control [ 55 ] and surveillance [ 56 ], CHWs urged for more OH training on multidisciplinary teamwork. Thus, the OH training should strengthen social and leadership skills, as well as training on coordinating roles in a multidisciplinary team along with the subject knowledge.…”
Section: Discussionmentioning
confidence: 99%
“…Although CHWs were trained for the selected zoonoses or participated in the zoonoses campaigning in the local setting, they urged for more intense OH training before being captivated as OHAs. Although the evidence already indicates the involvement of CHWs in pandemic control [51] and their multidisciplinary roles in infectious disease control [52] and surveillance [53], CHWs urged for more OH training on the multidisciplinary teamwork. Thus, the OH training should strengthen social and leadership skills, as well as training on coordinating roles in a multidisciplinary team along with the subject knowledge.…”
Section: Discussionmentioning
confidence: 99%
“…For emergency services, such as trauma or obstructed labor, patients are often able to pool resources from friends and family to arrange transport. Even then, our previous work has shown that more than half of pediatric deaths still occur in the home, largely because patients are not able to reach a clinic or hospital 10 .…”
Section: Study Populationmentioning
confidence: 99%